(untitled) (The International Journal for Scientific Research, 2024)
This study examines how e-wallets in Riyadh, Saudi Arabia, are influencing consumer buying patterns and money management. The study, which is based on Saudi Vision 2030, which prioritises financial inclusion and economic diversification, looks at how e-wallets affect young to middle-aged users’ financial discipline, impulsive buying habits, and purchase decisions. The users’ ages range from 22 to 35. Data was collected from 750 individuals using a cross-sectional survey strategy, and descriptive and inferential statistical techniques, such as regression analysis, were used for analysis. The results show that e-wallet adoption has a statistically significant positive impact on consumer purchasing patterns and money management. Convenience, real-time transaction capabilities, and spending tracking tools are some of the e-wallet characteristics that encourage both impulsive purchases and better budgeting techniques. According to the correlation analysis, there is a 0.734% increase in consumer buying behaviour and a 0.603% improvement in financial management for every 1% increase in e-wallet use. Because of their convenience of use and promotional incentives, e-wallets have the potential to simplify financial transactions, but they also provide a risk of excessive spending. In order to reduce the hazards associated with impulsive spending, the study’s conclusion highlights the significance of increasing consumer knowledge regarding appropriate e-wallet usage and financial education. Enhancing technology infrastructure, improving e-wallet features for increased user pleasure, and creating regulations that strike a balance between innovation and consumer safety are some of the recommendations. In line with the goals of Vision 2030, these findings advance knowledge of the changing dynamics of digital payments and its consequences for financial inclusion, personal finance, and overall economic growth. This study offers useful information to help stakeholders—such as customers, financial institutions, e-wallet providers, and legislators—make the most of digital payment systems and encourage prudent financial practices. To further enhance the conversation on digital payment ecosystems, future studies should examine sector-specific adoption trends and longitudinal effects.